Virtual focus groups among individuals with use disorders: assessing feasibility and acceptability in an underserved clinical population - Bergeria, Cecilia L.; Park, Brandon; Satyavolu, Prem Umang; Dunn, Kelly E.; Dworkin, Robert H.; Strain, Eric C. (Frontiers in Psychiatry, 2024)
Objective: There are substantial barriers to conducting research among individuals with stigmatized and complicated health conditions like substance use disorders. These barriers slow progress when developing, refining, and assessing interventions to better treat underserved populations. Virtual focus groups are an innovative method for collecting data from individuals via a discreet and accessible platform which can inform novel as well as existing treatment approaches. This article reports on the feasibility and acceptability of virtual focus groups as a mechanism to recruit and engage geographically and demographically diverse samples of participants with substance use disorders that are otherwise logistically difficult to assess.Method: Participants were assessed for eligibility for a virtual focus group study based on demographic features, drug use history, and psychiatric history via a remote, interview-based screening. Focus groups were completed anonymously without video or name-sharing.Discussion contributions, quantified with number of times speaking and total number of words spoken, were compared across gender, and treatment status. Participants provided quantitative and qualitative feedback on the focus group experience in a follow-up survey.Results: Focus groups (N=26) based in geographical areas throughout the United States were conducted with 88 individuals with opioid use disorder or stimulant use disorder.Discussion contributions were comparable between genders and among individuals in treatment versus those seeking treatment. A follow-up survey (n=50, 57% of focus group participants) reflected high levels of enjoyment, comfort, and honesty during focus group discussions. Discussion: Findings suggest virtual focus groups can be an effective and efficient tool for substance use research.